What Got You Here, Won’t Help You There: Changing Requirements in the Pre- Versus the Post-tenure Career Stage in Academia - Rehbock, Stephanie K.; Knipfer, Kristin; Peus, Claudia (Frontiers in Psychology, 2021)
Despite efforts to foster gender equality in academia, women are vastly under-represented in tenured professorships, specifically in STEM disciplines. While previous research investigated structural and organizational barriers for women in academia, we explored professors’ subjective view on attributes required before and after reaching tenure. The perspective of professors is needed as they are gatekeepers when it comes to the career advancement of junior researchers. Hence, we interviewed 25 tenured STEM professors in Germany about which attributes they personally consider to be required pre- versus post-tenure and analyzed whether these attributes are associated with gender stereotypes. We found that different attributes are mentioned in the pre- versus the post-tenure career stage and that the required attributes can be associated with gender stereotypes: While agentic–stereotypically male–attributes were mentioned more frequently than communal attributes in the pre-tenure career stage, communal–stereotypically female–attributes were reported slightly more often than agentic attributes after reaching tenure. Based on these novel findings, we discuss important implications for gender research and practice to contribute to more diversity and transparency in academic career advancement.